THE EFFECT OF AN INTEGRATED AFFECTIVE-COGNITIVE TEACHING AND LEARNING APPROACH ON ACADEMIC ACHIEVEMENT, SELF-EFFICACY, LOCUS OF CONTROL AND ATTITUDE TOWARDS ENGINEERING - Lashari, Tahira Anwar; Alias, Maizam; Kesot, Mohd Jahaya; Akasah, Zainal Abidin (Journal of Technical Education and Training, 2014)
Engineers are responsible for the sustainable development of society and to be effective in their role they must possess holistic skills that encompass the skills of the affective and the cognitive domain. Therefore, engineering education must place equal emphasis on the needs of the affective domain in addition to the needs of the cognitive domain. However, existing engineering education practices do not pay adequate attention to the needs of the affective domain. Therefore, the study seeks to determine the effect of a teaching and learning approach that integrates the affective and the cognitive learning needs on academic achievement, locus of control, self-efficacy, and attitude towards engineering. A quasi-experimental design study with pre and post-test was conducted on 70 engineering students who were enrolled in the Diploma of engineering programme in the Universiti Tun Hussein Onn Malaysia with n=36 and n=34 for the experimental and control group respectively. The results indicate that the experimental group was better on the achievement test and attitude measure compared to the control group and the academic improvement was most noticeable among the low achievers. In conclusion these results indicate that an integrated affective-cognitive learning approach can be used to induce simultaneous improvements in learning of the cognitive and affective domain.